Interaction Mechanisms Between Major Depressive Disorder and Non-alcoholic Fatty Liver Disease - Shao, Qi; Wu, Yiping; Ji, Jing; Xu, Tian; Yu, Qiaoyu; Ma, Chongyang; Liao, Xuejing; Cheng, Fafeng; Wang, Xueqian (Frontiers in Psychiatry, 2021)
Major depressive disorder (MDD), which is highly associated with non-alcoholic fatty liver disease (NAFLD), has complex pathogenic mechanisms. However, a limited number of studies have evaluated the mutual pathomechanisms involved in MDD and NAFLD development. Chronic stress-mediated elevations in glucocorticoid (GC) levels play an important role in the development of MDD-related NAFLD. Elevated GC levels can induce the release of inflammatory factors and changes in gut permeability. Elevated levels of inflammatory factors activate the hypothalamic–pituitary–adrenal (HPA) axis, which further increases the release of GC. At the same time, changes in gut permeability promote the release of inflammatory factors, which results in a vicious circle among the three, causing disease outbreaks. Even though the specific role of the thyroid hormone (TH) in this pathogenesis has not been fully established, it is highly correlated with MDD and NAFLD. Therefore, changing lifestyles and reducing psychological stress levels are necessary measures for preventing MDD-related NAFLD. Among them, GC inhibitors and receptor antagonists may be key in the alleviation of early and mid-term disease progression. However, combination medications may be important in late-stage diseases, but they are associated with various side effects. Traditional Chinese medicines have been shown to be potential therapeutic alternatives for such complex diseases.